A Randomized Trial of the Effects of Ambient Operating Room Temperature on Neonatal Morbidity - Ambia, Anne M.; Duryea, Elaine L.; Wyckoff, Myra H.; Tao, Weike; McIntire, Donald D.; Seasely, Angela R.; Moussa, Moussa; Leveno, Kenneth J. (American Journal of Perinatology, 2023)
Objective Newborn hypothermia has been implicated in neonatal morbidity without randomized evidence that it compromises the infant. Our objective was to determine if a difference in operating room temperature at cesarean birth impacts neonatal morbidity.Study Design Women undergoing cesarean delivery of a liveborn infant without major malformations were included. The institutional preexisting operating room temperature of 20°C (67°F) was compared with an experimental group of 24°C (75°F) by cluster randomization assigned on a weekly basis. Newborn hypothermia was defined as axillary temperature on arrival to the nursery of less than 36.5°C (<97.7°F). The primary outcome was a composite of neonatal morbidity including respiratory support, sepsis, hypoglycemia, and neonatal death.Results Between November 2016 and May 2018, 5,221 women had cesarean deliveries at Parkland Hospital with 2,817 randomized to the standard care group and 2,404 to the experimental group. The rate of neonatal composite morbidity did not differ between the groups: standard care 398 (14%) versus experimental 378 (16%), p = 0.11. This was despite a significant decrease in the rate of neonatal hypothermia: standard care 1,195 (43%) versus experimental 414 (18%), p < 0.001. There was no difference in the composite outcome for preterm infants (<37 wk) between the groups: standard care 194 (49%) versus experimental 185 (54%), p = 0.25.Conclusion An 8°F increase in operating room temperature was significantly associated with a reduced rate of neonatal hypothermia, although this decrease was not associated with a significant improvement in neonatal morbidity. However, the increase in operating room temperature was met with resistance from obstetricians and operating room personnel. This trial is registered (registration no.: NCT03008577).
Keywords: neonatal hypothermia; cesarean section; neonatal morbidity